Characteristic and Chemical Compound of charcoal Cocoa Wasted by Pyrolysis Process - Wijaya, Mohammad; Pari, Gustan; Amal (Al-Kimia, 2024)
Indonesia continues to experience a decline in cocoa production due to the aging of cocoa plants, conversion of cocoa plantations, pests, and diseases, as well as the government’s focus on food crops. These factors contribute to the problem of decreasing cocoa yields. The objectives of this research are to develop the production of cacao tea from cocoa leaves as a natural herbal drink, and to identify bioactive chemical compounds resulting from the pyrolysis of cocoa waste by controlling temperature and time. The methodology employed in this study includes the analysis of lignin, cellulose, and hemicellulose content in cocoa leaves. The pyrolysis process was conducted at 300°C, 400°C, and 500°C. Extraction was performed using an extractor, where the cocoa leaf waste was mixed with water heated to 80°C for 3 hours. The analysis of flavonoid and antioxidant levels in Pinrang cocoa leaves revealed lignin levels of 43.13%, holocellulose content of 47.11%, alpha-cellulose content of 31.13%, and cellulose content of 43.13%. Proximate analysis of Kolaka Regency cocoa leaves indicated phenol levels of 529.52 mg/kg, catechin levels of 615.71 mg/kg, glucose content of 6.68%, caffeine content of 329.56 mg/kg, carbon content of 52.20%, nitrogen content of 1.24%, hydrogen content of 17.55%, and oxygen content of 29.01%. For cocoa leaf extract from Pinrang Regency, the total flavonoids were 6.01% w/w, while for Kolaka Regency, the total flavonoids were 35.10% w/w. The utilization of cocoa leaves from Kolaka Regency demonstrated superior antioxidant content compared to those from Pinrang Regency. This indicates that cacao tea products made from Kolaka Regency cocoa leaves have great potential for development as a herbal drink. However, there has been limited research on this topic, particularly regarding the use of cocoa waste for cacao tea products.